Study on life and path of fatigue cracks in multiple site damage plates. (November 2015) - Seifi, Rahman; Ghadimian, Oshin; Ranjbaran, Milad
Highlights: The interaction of MSD cracks and holes reduce the overall fatigue life. Increasing the holes distances and decreasing their sizes increase the fatigue life. Under the little changes in the thickness, fatigue lives do not varied significantly. Effect of the thickness can be observed in the crack initiation in the experiments. Distance between holes altered the fatigue lives more than the size of the holes. Abstract: This paper presents experimental and numerical study of the fatigue crack growth of hollowed pre-notched plates with multiple site damages (MSD). The numerical analyses were performed using finite element method. Experiments were carried out to validate the numerical results. Fatigue tests of aluminum sheets with MSD cracks were conducted to evaluate the effects of some parameters such as the thickness, hole diameter and central distance of the holes. The results show that the distance of the holes has greatest and size of the hole has little effects on the fatigue lives. Nucleation of cracks strongly depends on the thickness, distance and hole size.